2022
DOI: 10.21203/rs.3.rs-2230730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triterpenoids in aerenchymatous phellem contribute to internal root aeration and waterlogging adaptability in soybean

Abstract: Aerenchymatous phellem (AP) is important for internal aeration and adaptation to waterlogging in plants. Herein, the extensive accumulation of triterpenoids such as lupeol and betulinic acid was identified in AP. However, the biological and physiological roles of these triterpenoids in plants are largely unknown. Lupeol is converted from 2,3-oxidosqualene by lupeol synthase (LUS) and oxidized to betulinic acid. Functional analysis of LUS genes in soybean revealed that GmLUS1 is crucial for triterpenoid biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The triterpenoid profiles of LORE1 insertion mutant lines of L. japonicus accession Gifu B-129 ( Fukai et al., 2012 ; Urbański et al., 2012 ) were analyzed to investigate the effect of loss-of-function of either LjCPR1 or LjCPR2 genes. Based on a previous study, LUS and CYP716A s genes that are responsible for lupeol and betulinic acid production, respectively, were upregulated in secondary aerenchyma of hydroponic-cultured L. japonicus ( Suzuki et al., 2022 ) and soybean plants under flooded conditions ( Takahashi et al., 2022 ). Therefore, to investigate if plant culture condition affects LjCPRs’ involvement with specific CYPs, the Ljcpr1 and Ljcpr2-1 loss-of-function mutant lines were both cultured in soil and a hydroponic system.…”
Section: Resultsmentioning
confidence: 99%
“…The triterpenoid profiles of LORE1 insertion mutant lines of L. japonicus accession Gifu B-129 ( Fukai et al., 2012 ; Urbański et al., 2012 ) were analyzed to investigate the effect of loss-of-function of either LjCPR1 or LjCPR2 genes. Based on a previous study, LUS and CYP716A s genes that are responsible for lupeol and betulinic acid production, respectively, were upregulated in secondary aerenchyma of hydroponic-cultured L. japonicus ( Suzuki et al., 2022 ) and soybean plants under flooded conditions ( Takahashi et al., 2022 ). Therefore, to investigate if plant culture condition affects LjCPRs’ involvement with specific CYPs, the Ljcpr1 and Ljcpr2-1 loss-of-function mutant lines were both cultured in soil and a hydroponic system.…”
Section: Resultsmentioning
confidence: 99%
“…The role of aerenchyma, including SA, is to supply air to roots under flooded conditions (Colmer & Pedersen, 2008; Shimamura et al ., 2010; Takahashi et al ., 2014). Our recent study revealed that G. max also accumulated BA in SA under flooded conditions and suggested that the accumulation of hydrophobic BA was essential to exclude water from gas spaces and promote air diffusion (Takahashi et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The triterpenoid profiles of LORE1 insertion mutant lines of L. japonicus accession Gifu B-129 (Fukai et al, 2012;Urbański et al, 2012) were analyzed to investigate the effect of loss-of-function of either LjCPR1 or LjCPR2 genes. Based on a previous study, LUS and CYP716As genes that are responsible for lupeol and betulinic acid production, respectively, were upregulated in secondary aerenchyma of hydroponic-cultured L. japonicus (Suzuki et al, 2022) and soybean plants under flooded conditions (Takahashi et al, 2022). Therefore, to investigate if plant culture condition affects LjCPRs' involvement with specific CYPs, the Ljcpr1 and Ljcpr2-1 loss-of-function mutant lines were both cultured in soil and a hydroponic system.…”
Section: Ljcpr1 and Ljcpr2-1 Loss-of-function Mutant Plantsmentioning
confidence: 99%